Impact of nitrogen fertilizer application on nitrous oxide emission in oil palm plantation - Mat Akhir, Nurul Izzati; Mohd Kusin, Faradiella; Mohamat-Yusuff, Ferdaus; Muhamad Awang,; Ash’aari, Zulfa Hanan (Elsevier, 2015)
This study investigates the impact of N-fertilizer application on the emission of nitrous oxide (N2O) in oil palm plantations. The soil sampling was undertaken at three different oil palm plantations of different land use, i.e. transformed land use (large and small-scale) and a logged-over forest. The soil samples were analysed for N, P and K contents and soil organic carbon. It was found that despite different amount of N-fertilizer applied at the plantations (in the range of 99-155 kg N/ha), immature palm development seems to release relatively higher amount of N2O compared to mature stage. However, further estimation of carbon equivalent emission (CO2-eq) would be a more useful means for estimating the impact of N-fertilizer on greenhouse gas emission